The optimisation of neural network parameters using Taguchi's design of experiments approach: An application in manufacturing process modelling - Wimalin Sukthomya (2018)
Neural networks have been widely used in manufacturing industry, but they suffer from a lack of structured method to determine the settings of NN design and training parameters, which are usually set by trial and error. This article presents an application of Taguchi's Design of Experiments, to identify the optimum setting of NN parameters in a multilayer perceptron (MLP) network trained with the back propagation algorithm. A case study of a complex forming process is used to demonstrate implementation of the approach in manufacturing, and the issues arising from the case are discussed. © Springer-Verlag London Limited 2005.